The comparison of side effects of methyldopa, amlodipine, and metoprolol in pregnant women with chronic hypertension - Masoumeh Ghafarzadeh; Amir Shakarami; Fatemeh Yari; Parsa Namdari (Taylor & Francis Group, 2020)
Objective The aim of the study was to compare the complication of Antihypertensive drug; in pregnant women with chronic hypertension. Method This retrospective cohort study was performed on 300 pregnant women  with chronic hypertension. Results:  a relative risk of preeclampsia among methyldopa group was 3.45 times higher than the metoprolol, the relative risk of preterm labor was not significantly between methyldopa and metoprolol group, LBW, and IUGR in methyldopa and amlodipine groups . Conclusion Methyldopa and amlodipine are associated with the least side effects in pregnant women treated for chronic hypertension.the incidence of preeclampsia was greater in methyldopa group.